2011
DOI: 10.5336/medsci.2010-21419
|View full text |Cite
|
Sign up to set email alerts
|

Does the Prevalence of Metabolic Syndrome in Pre- and Post-Menopausal Women Differ by the ATP III and IDF Criteria?

Abstract: A AB BS S T TR RA AC CT T O Ob b j je ec c t ti i v ve e: :The aims of this study we re the es ti ma ti on and com pa ri son of car di o vas cular risk fac tors and the pre va len ce of me ta bo lic syndro me (MetS) among pre-me no pa u sal (pre-M) and post-me no pa u sal (post-M) wo men. M Ma a t te e r ri i a al l a an nd d M Me et t h ho od ds s: : This study was con duc ted on 664 (pre-M: 378, post-M: 286) wo men, aged bet we en 30-64 ye ars. Body we ight and wa ist cir cum feren ces (WC) were measured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…In the primary search, 60 full text articles were related to our topic. After considering inclusion and exclusion criteria, 20 articles were included to qualitative analysis [8,15,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. In each selected study, the prevalence of MetS was reported according to different criteria; 17 reports based on NCEP ATPIII [8, 15, 18-29, 31, 33-35], 3 reports [22,27,32] based on IDF (2 reports were separately given prevalence data based on NCEP ATPIII and IDF criteria), 2 reports based on World Health Organization (WHO) and the other based on American Heart Association (AHA) [26,30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the primary search, 60 full text articles were related to our topic. After considering inclusion and exclusion criteria, 20 articles were included to qualitative analysis [8,15,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. In each selected study, the prevalence of MetS was reported according to different criteria; 17 reports based on NCEP ATPIII [8, 15, 18-29, 31, 33-35], 3 reports [22,27,32] based on IDF (2 reports were separately given prevalence data based on NCEP ATPIII and IDF criteria), 2 reports based on World Health Organization (WHO) and the other based on American Heart Association (AHA) [26,30].…”
Section: Resultsmentioning
confidence: 99%
“…Since, the related studies were found just from two countries of the Middle East region; Iran and Turkey, sub-group analysis was performed based on these countries. Among 17 studies, 11 reports were from Iran [8,15,18,20,21,23,24,27,28,33,34], and others were from Turkey [19,22,25,29,31,35].…”
Section: Resultsmentioning
confidence: 99%
“…According to the data of Turkish Adult Adults with Heart Disease and Risk Factors (TEKHARF), the prevalence of MetS in adults 30 years and older was 32.8% (38.6% in women and 27% in men) . Akbulut et al (2011) found that the incidence of MetS was 30.2% in premenopausal women and 47.6% in postmenopausal women according to the NCEP ATP III criteria. Kitiş et al (2010) found the incidence of MetS to be 31.9%.…”
Section: Discussionmentioning
confidence: 99%
“…[25,26] Premenopozal ve postmenopozal dönemdeki kadınlarda kardiyovasküler risk faktörleri ve MetS sıklığının karşılaştırılması amacıyla, 30-64 yaş arası 664 kadın ile yapılan bir çalışmada, postmenopozal kadınlarda MetS daha yüksek oranda saptanmış ve menopozun MetS için önemli bir risk faktörü olduğu sonucuna varılmıştır. [27] Brown et al (2008) tarafından yapılan çalışmada, postmenopozal kadınlarda anjiografi ile KVH tanısı almış 372 kadında, ATP III kriterlerine göre MetS prevalansı %70 bulunmuştur. [28] Diyabet, hipertansiyon ve kilo artışı menopoz sonrası dönemde kadınlarda KVH açısından ciddi birer risk faktörü olarak değerlendirilmelidir.…”
Section: Obeziteunclassified